2-D wavelength/time MDW code optimization for cardinality enhancement in OCDMA system - Amy Azura Mohamad Saufe (School of Computer and Communication Engineering, 2018)
The research work focused on the investigation of 2-D MDW code by using OCDMA technique. The development of the suggested codes was focusing on incoherent W/T coding based on the matrix combination way. This code is the evolution from one-dimensional (1-D) MDW code. The code with the mathematical calculation is in matrix system. The row is for the number of user and the column is for temporal code length. Nevertheless, this system also wants to overcome the noise for example shot noise, thermal noise and phase-induce intensity noise in term of deterioration of BER. The results are only based on the simulation and theory. All the simulation part was done by using the optical simulator Optical Communication System Design Software or Optisystem Version 7.0 from Optiwave.